Kandungan Buah Delima (Punica granatum L.) dalam Perspektif Al-Qur'an, Sunnah, dan Sains - Mansur, Sugeng Ali; Deroyeen, Ahmad Fauzan; Indriyanti, Muhfida Nur; Annisak, Alif Kammaliyyah; Fajriati, Devina Rizka; Amiruddin, Muhammad (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v2i0.2128, 2022)
The pomegranate is one of the many fruits mentioned by Allah SWT. in the Koran. Namely Q.S. Al-An'am verse 99 and Q.S. Ar-Rahman verse 68, with the term Al-rumman (Arabic). The pomegranate is special because it is one of the fruits of heaven. And when viewed from the world of empirical science, it turns out that almost all parts of this plant benefit the human body's health. Some important ingredients in pomegranate, such as vitamin C, ellagitannin (tannin), triterpenoids, flavonoids, and alkaloids, can function as antioxidants, antibacterials, antidiabetics and prevent cancer cells. Writing this article is expected to be able to enrich the treasures of modern health, which tends to be left only in the medical world, in addition to being an enrichment of knowledge about pomegranates both from an Islamic and health (medical) point of view.